2000
DOI: 10.1258/0022215001904644
|View full text |Cite
|
Sign up to set email alerts
|

Does it make sense to preserve the stapedial muscle during surgical treatment for otosclerosis?

Abstract: Our study aimed to show whether it is useful to preserve the stapedial muscle during the surgical treatment of otosclerosis. The study was carried out on 67 patients with tympanoscopic evidence of otosclerosis. In group A (34 patients) the stapedial muscle was intra-operatively preserved as follows: the stapedial suprastructure with preserved muscle tendon was transpositioned onto the longer arm of the incus and secured with a wire loop. The mean uncomfortable level for sounds was measured after surgery and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…This finding of stapedial tendon preservation stapedotomy was statistically significant which was quite similar to finding of Silverstain et al 10 Gross et al 14 and Rasmy et al 20 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding of stapedial tendon preservation stapedotomy was statistically significant which was quite similar to finding of Silverstain et al 10 Gross et al 14 and Rasmy et al 20 .…”
Section: Discussionsupporting
confidence: 90%
“…Audiometric test showed similar type of hearing outcome whether the tendon is preserved or not 12 . In the recent years, stapedial tendon preservation surgery has been advocated by some surgeons in hopes of obtaining better functional outcomes 11,14 .…”
Section: Introductionmentioning
confidence: 99%
“…There are a limited number of studies regarding how antidepressant and anxiolytic agents affect the reactions of the organism to light, sound, and tactile stimuli [1][2][3][4][5][6]. On the other hand, in the literature review, no studies regarding the effects of these drugs on the ASR were encountered.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been widely debated about a possible ST preservation during this procedure to prevent the devascularization and necrosis of the LPI. Although many authors have reported excellent objective and subjective results in patients who underwent to stapedectomy or stapedotomy with ST preservation, its usefulness is still controversial [13][14][15][16][17][18][19]. In addition, according to our findings, the BFD of the stapedial vessels seems to have an opposite direction to the LPI.…”
Section: Discussionmentioning
confidence: 43%